From texts to teeth: A multi-isotope study of sheep and goat herding practices in the Late Bronze Age ('Mycenaean') polity of Knossos, Crete. (February 2019) - Isaakidou, Valasia; Styring, Amy; Halstead, Paul; Nitsch, Erika; Stroud, Elizabeth; le Roux, Petrus; Lee-Thorp, Julia; Bogaard, Amy
Abstract: Linear B administrative documents of the late second millennium BC from urban Knossos, Crete, reveal that spatially extensive and centrally monitored sheep flocks and wool production played a fundamental role in Mycenaean palatial economy. Here we employ multi-isotope (δ 13 C, δ 18 O, 87 Sr/ 86 Sr) analysis of sequentially sampled sheep and goat tooth enamel bioapatite to explore life histories of animals consumed at Knossos. Interpretation of isotopic results incorporates new baseline data on 87 Sr/ 86 Sr ratios of bioavailable Sr from modern Cretan plants collected in relevant zones. Results reveal a variety of herding regimes, including seasonal ('wet/winter' to 'dry/summer') vertical movement of sheep from lowland to highland locations, more restricted mobility for goats in lowland to mid-altitude territories, possible input of fodder to goat diet, and exploitation of a range of plant ecosystems. Results broadly match documentary evidence and ethnographic/ecological expectations for sheep and goat herding at varying scales and underline the role of Knossos in mobilising resources from a range of herding systems and territories. Highlights: Isotopic analyses support Linear B evidence from 'Mycenaean' Knossos of large-scale sheep herding Measurement of modern plants provides baseline 87 Sr/ 86 Sr ratios of bioavailable Sr for various regions of Crete Sequential Sr, C and O analysis of tooth enamel reveals different herding regimes for sheep and goats Lower amplitude-attenuated maximum tooth enamel δ 18 O values suggest seasonal movement of sheep to high upland pastures Seasonally consistent δ 13 C values in goats may reflect winter foddering and/or grazing of coastal pastures